Association between household solid fuel use and cognitive frailty in a middle-aged and older Chinese population - Tan, Mo-Yao; Wang, Gao-Peng; Zhu, Si-Xuan; Jiang, Li-Hai (Frontiers in Public Health, 2025)
ObjectivesOur research intended to investigate the association between the solid fuels use and the risk of cognitive frailty (CF).MethodsThe research utilized data from the China Health and Retirement Longitudinal Study (CHARLS), a nationwide longitudinal study focusing on individuals aged 45 and older. A total of 8,563 participants without CF were enrolled from 2011 and followed up to 2015. Household fuel types include solid fuels (such as coal, crop residue, or wood-burning) and clean fuels (such as solar power, natural gas, liquefied petroleum gas, electricity, or marsh gas). CF was defined as the co-existence of cognitive impairment and physical frailty. Cox proportional hazards models were utilized to evaluate the relationship between the solid fuels use and the risk of CF. Furthermore, sensitivity analyses were conducted.ResultsOver a median follow-up of 4.0 years, 131 subjects were diagnosed with CF. We observed that the solid fuels use for cooking or heating increased the risk of developing CF compared to clean fuels, with HRs of 2.02 (95% CI: 1.25 to 3.25) and 2.38 (95% CI: 1.26 to 4.48), respectively. In addition, participants who use solid fuel for heating (HR: 2.38 [95% CI: 1.26, 4.48]) and cooking (HR: 2.02 [95% CI: 1.25, 3.25]) might experience an increased risk of CF. However, transitioning from solid to clean fuels for cooking could potentially reduce these risks (HR: 0.38 [95% CI: 0.16, 0.88]).ConclusionHousehold solid fuels utilization was closely associated with the risk of CF.